2012
DOI: 10.1051/matecconf/20120105002
|View full text |Cite
|
Sign up to set email alerts
|

Delayed dynamical sytem strongly coupled to a nonlinear energy sink : application to machining chatter

Abstract: Abstract. This paper investigate the different response regimes of a cutting tool on a lathe strongly coupled to a nonlinear energy sink. The equations of motion are analysed via the method of multiple scales. Condition of elimination of secular terms permit to derive equation of the slow invariant manifold (SIM) and the behavior of the system has been explained by studying the location of the fixed points of the slow flow on the SIM. Different types of responses are revealed such as periodic response and also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
(14 reference statements)
0
7
0
Order By: Relevance
“…Here, v and w are the physical quantities for the center of mass (with a factor of 1 þ e) and the relative displacement, respectively. Then, the equations of motion (22) become…”
Section: Analytical Study: Basins Of Attraction For Suppression Mechamentioning
confidence: 99%
See 1 more Smart Citation
“…Here, v and w are the physical quantities for the center of mass (with a factor of 1 þ e) and the relative displacement, respectively. Then, the equations of motion (22) become…”
Section: Analytical Study: Basins Of Attraction For Suppression Mechamentioning
confidence: 99%
“…They derived the equation of the slow invariant manifold (SIM) and explained the behavior of the system by studying the location of the fixed points of the slow flow on this manifold. Moreover, Gourc et al [22] have studied the passive control of chatter instability in turning processes using a vibro-impact nonlinear energy sink.…”
Section: Introductionmentioning
confidence: 99%
“…The behavior of an embedded NES on a lathe cutting tool has been previously studied in [12], it was shown that passive control of chatter by using a NES is possible and good correspondence between analytical prediction and numerical integration was observed. However, only a linear cutting law was considered.…”
Section: Analysis Of Some Response Regimesmentioning
confidence: 96%
“…The idea of attaching a nonlinear oscillator to a lathe is relatively new [11,12]. In recent studies, it has been demonstrated that addition of a small mass attachment with a strong nonlinear coupling (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation